THE EFFECT OF PRICE AND LOCATION ON CONSUMER PURCHASING DECISIONS AT TOKO ANGGUN BANGUNAN KULIM IN PEKANBARU CITY - Putri Anggun; Syahdanur (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to determine and analyze the effect of price and location on consumer purchasing decisions at Toko Anggun Bangunan Kulim, Pekanbaru City. The research method used is a quantitative method with descriptive and associative approaches. The population in this study were all consumers who had made purchases at Toko Anggun Bangunan, and the sampling technique used was accidental sampling, resulting in a sample of 100 respondents. Data collection was carried out through questionnaires, while data analysis used validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²) with the help of SPSS program. The results of the study indicate that partially the price variable has a significant effect on purchasing decisions, and the location variable also has a significant effect on purchasing decisions. Simultaneously, price and location have a significant effect on consumer purchasing decisions. The coefficient of determination shows that price and location variables are able to explain consumer purchasing decisions, while the rest is influenced by other variables not examined in this study.